2012
DOI: 10.1111/j.1530-0277.2012.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Persistent Effects of Ethanol Exposure on Development: An In Vivo Analysis During and After Embryonic Ethanol Exposure in Caenorhabditis elegans

Abstract: Background Defects caused by ethanol (EtOH) exposure during development can be different depending on the time of observation. To investigate this temporal component of developmental delay, we use the fast‐developing nematode model Caenorhabditis elegans. We first defined the longitudinal effects of EtOH on development using age‐appropriate markers and then closely followed embryonic development before, during, and after EtOH exposure. Methods C. elegans embryos were bathed in 0 to 20% EtOH (w/w in ddH2O) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Since most neurogenesis occurs during embryogenesis in C. elegans , MAP exposure was conducted during this critical period of neurobiological development. Other researchers have utilized similar exposure paradigms to examine the effects of embryonic drug exposure on development in C. elegans [57]. It is well established that MAP is neurotoxic to DA neurons and can lead to neurodegeneration in mammals [15], and the data presented here indicates that similar effects can occur in C. elegans .…”
Section: Discussionmentioning
confidence: 54%
“…Since most neurogenesis occurs during embryogenesis in C. elegans , MAP exposure was conducted during this critical period of neurobiological development. Other researchers have utilized similar exposure paradigms to examine the effects of embryonic drug exposure on development in C. elegans [57]. It is well established that MAP is neurotoxic to DA neurons and can lead to neurodegeneration in mammals [15], and the data presented here indicates that similar effects can occur in C. elegans .…”
Section: Discussionmentioning
confidence: 54%
“…Chronic exposure to EtOH in C. elegans results in delayed development, decreased reproduction, and shortened life span (Davis et al., ). Depending on the time point of EtOH exposure, defects in development vary in strength, suggesting that C. elegans could be used to identify the critical period during development at which EtOH exposure causes subsequent delays (Lin et al., ). In Drosophila , EtOH exposure during development results in reduced viability, slower development, and a reduced rate of neuroblast division, resulting in smaller brains.…”
Section: Studying the Action Of Etoh: Characteristics Of Etoh‐inducedmentioning
confidence: 99%
“…However, if ethanol is applied at a 0.4 M concentration, previous studies in adult C. elegans have shown that an internal ethanol concentration equivalent to 100 mg/dl can be reached (146). In studies that have used this model to examine the effects of ethanol on development, ethanol exposure produced, in a dose-dependent manner, significant growth retardation, slowed the developmental process, impaired reproduction, and lead to early demise in the offspring (145, 147) indicating that ethanol can have similar effects on development in C. elegans as in human beings. Future work using this model may be able to shed light into some of the genetic mechanisms of PNEE, and whether particular genes may confer sensitivity or resistance to the toxic effects of ethanol during development (145, 147).…”
Section: Factors To Consider When Modeling Fasdmentioning
confidence: 99%